The Effectiveness of Hypnobreastfeeding on the Success of Early Initiation of Breastfeeding in Efforts to Prevent Stunting - Urhuhe Dena Siburian; Paruhum Tiruon Ritonga (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Hypnobreastfeeding makes mothers feel calm, comfortable and happy so that the hormones prolactin and oxytocin increase which play a role in facilitating breast milk production. The hypnobreastfeeding technique increases mothers' confidence and motivation to breastfeed and carry out Early Breastfeeding Initiation (IMD). Improper implementation of IMD results in inadequate nutrition for babies at the start of life which can cause stunting. The results of the study show that babies who do not receive IMD have an impact on stunting. This research aims to determine the effectiveness of hypnobreastfeeding on the success of IMD. This type of research is Quasi Experimental with a case-control design. The sample consisted of 60 people, 30 people in each group, using a purposive sampling technique. The research was carried out in the working area of the Siatas Barita Community Health Center from March to September 2024. Bivariate data analysis used Independent Statistical Tests with a significance level of 95%. The success of implementing IMD in the case group was 86% (26 people) and in the control group was 53% (16 people). The results of the Independent Statistical Test, the p-value was 0.012 (α<0.05), meaning there was a difference in the effectiveness of hypnobreastfeeding on the success of IMD. It was concluded that hypnobreastfeeding was effective in the success of IMD. It is hoped that hypnobreastfeeding will be held in pregnant women's classes so that IMD can be successfully implemented as an effort to prevent stunting. Keywords :Early Initiation of Breastfeeding, Hypnobreastfeeding, Stunting